The Effect of Family Upbringing on Shaping Racial Behavior During the Infancy Stage: Child’s Lullaby As A Model - Kadhim, Libya Hussein Karim (Al-Adab Journal, 2022)
Childhood is a world that requires us to stand, contemplate, understand and study extensively, not to clarify what childhood is in general for society and define it in particular for the family and the mother, but rather to transcend errors in education and focus on modifying and modernizing the behavioral system of the child, to raise a generation that leans on tradition, a creative generation developed with its ideas that transcends racism and sectarianism Children are the future, they are the next social structure. Taking care of them and reflecting on their concerns means building a healthy, healthy, and healthy social pyramid that can move forward in development and progress. It seeks to reject extremism and tends to embrace the difference. Our societies have become fragile in terms of moral and social aspects. We surround ourselves with that false framework to hide The gravity of our mistakes, our return to education is the basis of social construction, and benefiting from the experiences of others in building their societies is the first correct step.